The use of artistic languages in the formative process of medical students: an academic experience (Research, Society and Development, 2022)
This paper aims to list the experiences regarding the use of the artistic languages as a learning instrument in medical classes at a university in the interior of Bahia, presenting the contributions of artistic methods in the learning of medical students for a training that enhances the humanization of future healthcare practitioners. This study is characterized as bibliographic and documental research, based on references about the theme, teaching plans and the documentation responsible for the course regiment; moreover, they were correlated with the theory of the learning content types established by Zabala (1999). As a result, a table was obtained containing the semester, curricular component, subject, type of teaching content and artistic language used. From the documental and referential analysis it was possible to observe that artistic methods contributed in a relevant way to the teaching of conceptual, procedural and attitudinal content. Therefore, it is concluded that there is a significant potential for the use of artistic languages in the process of medical training.